2022
DOI: 10.48550/arxiv.2205.04420
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Induced subgraphs and tree decompositions V. One neighbor in a hole

Abstract: What are the unavoidable induced subgraphs of graphs with large treewidth? It is well-known that the answer must include a complete graph, a complete bipartite graph, all subdivisions of a wall and line graphs of all subdivisions of a wall (we refer to these graphs as the "basic treewidth obstructions.") So it is natural to ask whether graphs excluding the basic treewidth obstructions as induced subgraphs have bounded teewidth. Sintiari and Trotignon answered this question in negative. Their counterexamples, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…• Over a series of papers, Abrishami et al recently studied induced obstructions to bounded treewidth (see [2,3,5,[7][8][9][10]12]). In particular, they showed that the class of (even hole, diamond, pyramid)-free graphs is (tw, ω)-bounded (see [9]).…”
Section: Introductionmentioning
confidence: 99%
“…• Over a series of papers, Abrishami et al recently studied induced obstructions to bounded treewidth (see [2,3,5,[7][8][9][10]12]). In particular, they showed that the class of (even hole, diamond, pyramid)-free graphs is (tw, ω)-bounded (see [9]).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the focus now is to determine which graph classes of unbounded degree have bounded treewidth. Several previous papers in this series have proven that certain hereditary graph classes of unbounded degree have bounded treewidth; see [1,4]. Graph classes in which treewidth is bounded by a logarithmic function of the number of vertices have also been studied ( [3,7]).…”
Section: Lemma 11 ([15]mentioning
confidence: 99%
“…For a graph H, let S H ⊆ V (H) denote the set of vertices of H of degree at least three. By Theorem 7.1 of [1], there exists a constant w(t, ∆) such that for every graph H, if H has treewidth at least w(t, ∆) and S H has maximum degree at most ∆, then H contains a subdivision of the (t × t)-wall or the line graph of a subdivision of the (t × t)-wall as an induced subgraph. We apply this theorem to G. By definition of strongly 2-bipartite, it follows that S G is a partite set of a bipartition of G, and thus has maximum degree 0.…”
Section: Lemma 45 Let T > 0 and Letmentioning
confidence: 99%
See 1 more Smart Citation